Unifying Art and Nature: Brady and Eco on Interpretation - L. Siani, Alberto (Aesthetica Preprint, 2020)
The issue of interpretation is a fundamental one in aesthetics, whether we are dealing with artworks or with natural environments. Whereas interpretation of art is an established topic in philosophy, this is less the case for interpretation of nature. Emily Brady’s article Interpreting Environments is an illuminating instance in this regard. While I mostly concur with the framework she proposes, in this paper I address two interconnected points that appear problematic and which derive from a postulated difference between artworks and nature as objects of interpretation. The first is the ad hoc introduction of a notion of respect for nature as an aim of our interpretive processes, juxtaposed to the pleasure we may gain from these processes themselves. The second is a still rather essentialistic or naively realistic conception of nature. I suggest that, by avoiding the above mentioned postulated difference, both points can be reformulated without prejudice to her overall approach and to its further development. To this aim I will establish a dialogue between Brady’s paper and Umberto Eco’s theses on interpretation in general and of literary texts in particular.